IDENTIFICATION OF THE DETERMINING FACTORS OF THE TAKE-OFF PHASE IN THE LONG JUMP USING 2-DIMENSIONAL BIOMECHANICS STUDY - Moh Nanang Himawan Kusuma; Tegar Pangudi (Majalah Ilmiah Olahraga, 2025)
The analysis of the long jump explains that the long jump consists of 4 phases namely the approach, take-off, flying, and landing. A running velocity in the approach phase often cannot be accelerated optimally in the last 3 steps due to a lack of take-off accuracy and improper technique based on biomechanical perceptions. The performance-limiting in the take-off phase such as run-up speed (va), take-off speed (vt), take-off angle (Î±t), and the height of the center mass (tb) have not been clearly identified. Method. This experimental study with a cross-sectional approach analyzes the profile of run-up speed (va), take-off velocity (vt), take-off angle (Î±t), and height of center mass (tb), including their correlation to the jump performance. 15 male athletes from the group of teenagers, juniors, and senior athletes were voluntarily tested using a 2-Dimensional biomechanical image capture sagittal view, equipped with informed consent, body mass index, leg length, and running speed of 30 meters. Results. Initial acceleration (p=0.002), take-off velocity (p=0.001), take-off angle (p=0.001), height of center mass  (p=0.001) were significantly proved affected to the long jump performance (p<0.05). The farthest jump has an average speed of the last 3 steps of 8.53 m/s, a take-off velocity of 7.73 m/s, a take-off angle (22.7°), and the height of the center of mass (109cm). Conclusion. Speed acceleration in the last 3 steps, the ability to take off at high velocity, and keep the center of body mass in height position are proven to significantly affect the performance, while the optimal take-off angle is largely determined by the anthropometric profile of each athlete.